Fischiare, una metafora: lingua e scrittura di un premio letterario. (Gilgameš, 2019)
Numerous are the comparisons that contemporary literature opens up to styles, genres and words of tradition. The dichotomy that distinguishes the choices of writing between a norm and a misrepresentation of the same has left (now perhaps more openly) the non-place of the linguistic standard emerging as a directional matrix of a more spontaneous communication, which aims to approach the competences - or presumed such - of the reader. The analysis chooses to investigate the pages of La vita prodigiosa di Isidoro Sifflotin as the winner of the Campiello Opera Prima Award in 2015; what is proposed is therefore a linguistic reasoning that can interrogate the pages of the novel to understand what expedients and narrative mechanisms have led to assign a certain literary validity to a product that, deliberately, does not choose the linguistic literary standard. .